The theoretıcal ımplıcatıons of job demands resources model: a research study on the relatıons of job demands, supervısor support and job autonomy wıth work engagement - (:unkn) unknown (My University, 2014)
Özet: Bu çalışmanın amacı iş taleplerinin (iş yükü, rol çatışması, rol belirsizliği, iş güvencesizliği) and iş kaynaklarının (yönetici desteği ve iş otonomisi) Türkiyede sağlık kurumlarında görev yapan hemşirelerin işe gönülden adanma düzeyi ile ilişkilerinin incelenmesidir. Elde edilen sonuçlar iş yükünün dinçlik ve adanmışlık ile negatif yönde ilişkili, iş güvencesizliğinin ise dinçlik, adanma ve yoğunlaşma ile negative yönde ilişkili olduğunu göstermiştir. Amir desteğinin işe gönülden adanmanın çoşku ve adanmışlık boyutları ve toplam gönülden adanmışlık ile güçlü seviyede ilişkili olduğu, otonominin orta derecede etkiye sahip olduğu, rol belirsizliğinin ise coşku, adanmışlık ve toplam gönülden adanmışlık üzerinde orta derecede etkiye sahip olduğu belirlenmiştir. Tüm bu elde edilen sonuçlara gore, iş yükü, role belirsizliği, rol çatışması ve iş güvencesizliği algılarından olşaun iş taleplerinin ve otonomi ile amir desteğinden oluşan iş kaynaklarının hemşirelerin işe gönülden adanma algıları ile anlamlı bir ilişkisinin olduğu görülmüştür.

Abstract: The purpose of this study is to examine how job demands (work overload, role conflict, role ambiguity, job insecurity) and job resources (supervisor support and job autonomy) are related to work engagement of nurses working in Turkish Health Organizations. The findings revealed that work overload had a negative relationship with vigor and dedication and job insecurity had significant negative relationships with vigor, dedication, and absorption. It was determined that supervisor support had significant large effect relationships with vigor, dedication, and UWES total. Job autonomy had medium effect relationships with vigour, dedication and UWES total, role ambiguity showed a medium effect relationship with vigor, dedication, and UWES total. Job insecurity and role ambiguity displayed negative relationships with vigor, dedication, and absorption. Based on the findings, the suggestions of the study were supported and it was concluded that perceived job demands as measured with work overload, role ambiguity, role conflict, and job insecurity and job resources as measured with supervisor support and job autonomy had significant relationships with work engagement of nurses. .
İş talepleri-kaynakları modeli: iştaleplerinin, yönetici desteğinin ve otonominin işe gönülden adanma ile ilişkileri üzerine bir araştırma
Keywords: İktisat; İşletme